2000
DOI: 10.1143/jjap.39.l1259
|View full text |Cite
|
Sign up to set email alerts
|

Defect Control for Large Remanent Polarization in Bismuth Titanate Ferroelectrics –Doping Effect of Higher-Valent Cations–

Abstract: The effects of concentration and distribution of defects controlled by quenching and doping of higher-valent cations on the ferroelectric properties of dense Bi4Ti3O12 ceramics were investigated. The remanent polarization (P r) of non-doped ceramics quenched from 800°C (above the Curie temperature) was twice as large as those of samples subjected to slow cooling to 25°C and quenched from 600°C (below the Curie temperature). These results imply that domain pinning by defects dominates the pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
187
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(199 citation statements)
references
References 11 publications
10
187
0
2
Order By: Relevance
“…The variation of P r and E c on La content (x) could be explained in terms of the changing oxygen vacancy concentration in the system. It is reported that oxygen vacancies are created due to bismuth loss, and under high electric fields the mobile oxygen vacancies can assemble at the lowest energy domain walls and thereby hinder polarization switching due to domain pinning [37]. At higher La content x [ 0.15, the decrease in P r was attributed to the relaxation in structural distortion as noted from X-ray and Raman spectroscopy study.…”
Section: Dielectric Studymentioning
confidence: 85%
“…The variation of P r and E c on La content (x) could be explained in terms of the changing oxygen vacancy concentration in the system. It is reported that oxygen vacancies are created due to bismuth loss, and under high electric fields the mobile oxygen vacancies can assemble at the lowest energy domain walls and thereby hinder polarization switching due to domain pinning [37]. At higher La content x [ 0.15, the decrease in P r was attributed to the relaxation in structural distortion as noted from X-ray and Raman spectroscopy study.…”
Section: Dielectric Studymentioning
confidence: 85%
“…[9][10], and the 2Pr value was smaller and the Ec value was larger than those reported in [31]. Based on above results, it was found that the simultaneous substitutions for B-site are effective to derive enough ferroelectricity by accelerating the domain nucleation and pinning relaxation caused by B-site substitution [32][33][34][35]. According to pervious study, the Bi 4 Ti 3 O 12 materials exhibit high leakage current and domain pinning properties because of the defects such as bismuth and oxygen vacancies.…”
Section: The Influence Of Doping Effect On the Electrical Properties mentioning
confidence: 85%
“…In addition, the B-site substitution by high-valent cation was mainly the compensation for the defects. These defects caused by the fatigue phenomenon and strong domain pinning [37][38][39][40].…”
Section: The Influence Of Doping Effect On the Electrical Properties mentioning
confidence: 99%
“…[101] reported a remarkable improvement in ferroelectric properties in the Bi 4 Ti 3 O 12 ceramic by adding higher valent cation, V 5+ at the Ti 4+ site. Recently, significantly large P r value has been reported for W-substituted BIT sintered sample [102]. It has also been reported that cation vacancies generated by donor doping make domain motion easier and enhance the ferroelectric properties [103].…”
Section: Ferroelectric Propertiesmentioning
confidence: 99%